2017
DOI: 10.22236/jer_vol2issue2pp115-129
|View full text |Cite
|
Sign up to set email alerts
|

L2 Writing Strategies Used by EFL Graduate Students

Abstract: This study investigates the writing strategies and the predominantly strategies used by four Indonesian graduate students when writing in L2 (English). They were divided into 2 groups, skilled and less skilled writers, to examine what strategies they applied when writing. The main instrument of this study is Think Aloud Protocols (TAPs). The analysis of data collected discovered some findings: (1) both skilled and less skilled writers used varied strategies. However, the frequency of using each strategy was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Asmari (2013), also claimed that writing strategies is a factor that gives impact on students during the writing process as well as helps students to solve the problem in writing. Moreover, Arifin (2017) argued that writing strategies are individual strategies adopted by writers to overcome their problems during writing processes. Thus, there is an urgent need for EFL students to have writing strategies because those things are important in the academic world and in the professional field (Arifin, 2017;Asmari, 2013;Lili, 2015;).…”
Section: Introductionmentioning
confidence: 99%
“…Asmari (2013), also claimed that writing strategies is a factor that gives impact on students during the writing process as well as helps students to solve the problem in writing. Moreover, Arifin (2017) argued that writing strategies are individual strategies adopted by writers to overcome their problems during writing processes. Thus, there is an urgent need for EFL students to have writing strategies because those things are important in the academic world and in the professional field (Arifin, 2017;Asmari, 2013;Lili, 2015;).…”
Section: Introductionmentioning
confidence: 99%
“…Students actually have personal strategies to overcome their problems during writing processes (Arifin, 2017). For instance, they started by brainstorming ideas through books or articles after they understood the demand of writing task.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies conducted by Chen (2011), Maarof & Murat (2013), Mohite (2014), and Arifin (2017) revealed that students both in school and university in any level used various kinds of writing strategies to achieve their goal in writing in the terms of writing process or six writing strategies proposed by Oxford. Then, proficient writers done many revision steps (Qamariah, 2016) and applied more strategies (Arifin, 2017) than compared to less proficient writers. In addition, proficient writers mostly used reading and rereading strategies for several purposes such as revising and editing the text, developing ideas, and getting new ideas (Arifin, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: writing, revision, teacher comments Innledning Det er et gjennomgående funn i skriveforskningsfeltet at tekstrevisjon er viktig for å skape tekster av høy kvalitet. Sterke skrivere reviderer mer og på andre måter enn svakere skrivere, og gode tekster blir som regel til over tid og etter flere revisjoner (Arifin, 2017;Bereiter & Scardamalia, 1987;Carey & Flower, 1989;Dysthe & Hertzberg, 2014;Kellogg, 1999). Det har derfor vaert stor interesse i den skrivedidaktiske forskningen for å undersøke hvordan barn og unges kompetanse i tekstrevisjon utvikles i skole og høyere utdanning, og hvordan laerere best kan fremme denne utviklingen, blant annet gjennom de tilbakemeldingene de gir på elevers og studenters tekster.…”
unclassified